THE ROLE OF CULTURE AND HERITAGE IN THE TOURISM INDUSTRY (Conferencea, 2022)
It is known that demands and proposals have been developed for all problems in the development of tourism in our country. Also, innovations in the field of tourism and all systemic events that lead to positive changes that ensure the sustainable development of tourism are reflected. Also, the role of culture and heritage in the tourism industry is one of them. This article is about it.